Kriminolojide çoklu öldürmeler - Artuk, Mehmet Emin (İstanbul Medipol Üniversitesi, 2019)
Toplu öldürmeler üç kategoriye ayrılmaktadır: Toplu katliam, aynı yerde duygusal süreç içinde birden fazla kişinin öldürülmesidir. Çılgın cinayet ise, farklı yerlerde birinci kategori gibi duygusal soğuma süreci gerçekleşmeden birden fazla kişinin öldürülmesidir. Bu kişiler, birinci gruptakiler gibi rastgele seçilmiş kimseler olabilir. Seri cinayetler ise, literatürde sayısal farklılıklar bulunmasına rağmen, bir kişinin birden fazla kişiyi ayrı yerlerde duygusal soğuma süreci içerisinde rastgele öldürmesidir. Bu süreç gün, ay ve hatta yıllar sürebilir. Fail kurbanları unutmamak için onlardan bir hatıra obje da alabilir.

Mass killings are divided into three categories: Mass murder is the killing of more than one person in the emotional process in the same place. Spree murder is the killing of more than one person in different places without the emotional cooling process as in the first category. They, the victims, may be randomly selected as in the first group. Serial murder, although there are numerical differences in the literature, is that one person randomly kills more than one person in separate places in the process of emotional cooling. This process may take days, months or even years. The perpetrator may also receive a commemorative object from them in order not to forget the victims.
Mass killings in criminology
Keywords: Toplu Cinayet; Çılgınlık Cinayeti; Seri Cinayet; Seri Katil; Mass Murder; Spree Murder; Serial Murder; Serial Killer